Peramalan Jumlah Penderita DBD di Provinsi Jawa Barat dengan Metode Hybrid Sarimax-Ann - Indriany Rahayu; Rini Marwati; Dewi Rachmatin (JMT : Jurnal Matematika dan Terapan, 2022)
Indonesia is one of the tropical countries in the world, therefore Indonesia has two seasons, namely the dry season and the rainy season. Because it has two seasons, it can cause tropical diseases that is growing very fast is Dengue Hemorrhagic Fever (DHF). DHF is time series data tha can be collected annually and has a seasonal cycle. Because it is time series data, it can be forecasted using SARIMAX method, but SARIMAX is only able to solve linear problems and to overcone non-linear prolblems it can be solved using the ANN Backpropagation method. Therefore, in this study using the Hybrid SARIMAX-ANN method. The data in this study contained the dependent variable and the independent variable. The dependent variable is DHF data, while the independent variable is air humidity, air temperature, and rainfall data. The result obtained in this study, namely the factor that greatly affects DHF is air humidity. Forecasting result form Januari 2021 to June 2021 are 1.081, 960, 1.132, 1.103, 2.467, and 1.605. the it produces a MAPE value of 16,33% which means a good level of accuracy.